The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.2147/vhrm.s49118
|View full text |Cite
|
Sign up to set email alerts
|

Safety, tolerability, and efficacy of a fixed-dose combination of olmesartan 40 mg and hydrochlorothiazide 12.5/25 mg in daily practice

Abstract: BackgroundThe safety and efficacy of olmesartan 40 mg and hydrochlorothiazide (HCTZ) as a fixed-dose combination has been investigated in clinical trials leading to its approval. The aims of the present study were to confirm these data in an unselected patient population in daily practice and to determine the impact of physical activity on blood pressure control.MethodsIn a multicenter, noninterventional study, 3,333 patients with either insufficient blood pressure control on olmesartan 40 mg alone or on a fix… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 30 publications
0
6
0
2
Order By: Relevance
“…Combination therapy may lower pill burden and improve adherence and clinical outcomes in some cases, without an increase in costs [170]; acceptability to therapy may be high, but discontinuation of medications, nevertheless, still occurs [171]. Combination therapy may also help synergistic enhancement of drug effects and reduction in adverse effects, with positive influence on safety and tolerability [104,172,173]. Triple fixed-dose combination therapy with an ARB, a CCB, and a thiazide favorably impact BP control [174].…”
Section: Referencesmentioning
confidence: 99%
“…Combination therapy may lower pill burden and improve adherence and clinical outcomes in some cases, without an increase in costs [170]; acceptability to therapy may be high, but discontinuation of medications, nevertheless, still occurs [171]. Combination therapy may also help synergistic enhancement of drug effects and reduction in adverse effects, with positive influence on safety and tolerability [104,172,173]. Triple fixed-dose combination therapy with an ARB, a CCB, and a thiazide favorably impact BP control [174].…”
Section: Referencesmentioning
confidence: 99%
“…Diuretic : Although the combination of diuretics and ACEI/ARB has been merged as one of the most common regimes in treating hypertension, the role of diuretics on treating arterial stiffness has not been well explored. 58 77 A 4-week study demonstrated that hydrochlorthiazide failed to decrease PWV and AIx in spite of a reduction in brachial BP, which imply no favourable effect of diuretics on arterial stiffness beyond BP reduction. 76 …”
Section: The De-stiffening Therapy and Stroke Preventionmentioning
confidence: 99%
“…Studies of OLM, both as monotherapy and, to a greater extent, as a component of combination therapies, have consistently demonstrated that it has a better tolerability profile than placebo and that the risk of drug-related adverse events is at least comparable to that with other ARBs and lower than with any other antihypertensive drug class, including diuretics [ 46 49 ]. Of note, the incidence of drug-related adverse events was largely independent of dose titration and was, in fact, lower when the drug was used in fixed-dose combination therapies with HCTZ, AML or both [ 46 49 ].…”
Section: Specific Forms Of Hypertensionmentioning
confidence: 99%